Assessing the heterogeneous source of the Azores mantle plume - Felix S. Genske (2020)
The Azores islands in the central North-Atlantic are the subaerial parts of a large oceanic plateau that is best explained by the presence of a mantle plume that arrived in the vicinity of the Mid-Atlantic ridge (MAR) some 40 Ma ago. Recent volcanic activity either side of the MAR implies that this plume is still feeding volcanism on the islands today. Much work has therefore focused on the nature of the magmatism on both the islands and the MAR. Significant geochemical heterogeneity is observed in the ocean islands basalts (OIB) from the eastern islands implying similar heterogeneity in the plume itself. However, there has, to date, been little information available from the islands situated to the west of the MAR. This thesis has two foci and associated aims. The first encompasses the petrology and geochemistry of lavas from the western Azores islands of Flores and Corvo and forms the basis of the second chapter. Subsequently, the data obtained from these islands is incorporated with published data from the eastern islands and MAR into a broader assessment of the mantle source composition across the plateau. This second focus encompasses perspectives from both radiogenic and stable isotopes. Across plateau variations of Sr-Nd-Hf-Pb-Os and B-O-Li isotope ratios are assessed. Chapter three reveals important clues for the characterization of the mantle source of OIB from oxygen isotopes from olivine phenocrysts. In chapter four, the light elements lithium and boron and their isotopic composition are investigated in primitive lavas that are otherwise well characterized. The processes of assimilation fractional crystallization (AFC) show to be important in accounting for the variability that is observed on each island. Stripping-off these effects is crucial for characterization of the primary mantle signal of these OIB. Chapter five combines this information with Hf-Pb-Os isotopes and trace-element variations across the plateau. Evidence for melting of carbonated peridotite on Santa Maria Island, which is the ...